Perbaikan Jalan Tanjakan Desa Air Putih Kecamatan Talang Empat Kabupaten Bengkulu Tengah - Ridianto, Ridianto; Solichin, Solichin; Mulyadi, Mulyadi; Putra, Muhammad Bima Eka; Faridah, Faridah (STIA Bengkulu, 2022)
Roads are very important land transportation infrastructure because they support community access from one area to another. Community Service Activities in Air Putih Village, Talang Empat District, Central Bengkulu, precisely on the road connecting Air Putih Village Dusun II to Hamlet I. This village road is the access to and from the Air Putih Village community apart from the villagers from the Air Sebakul highway. The method used is a survey carried out to find out how severe the damage and the number of damaged road locations are, after that planning makes the tasks of each Member of Service Activities, carrying out road repairs along the 100 m final stage of evaluation to find out the response of the surrounding community.